Liver Fibrosis‐4 index indicates atrial fibrillation in acute ischemic stroke. (24th May 2022) - Fandler‐Höfler, Simon; Kneihsl, Markus; Stauber, Rudolf E.; Bisping, Egbert; Mangge, Harald; Wünsch, Gerit; Haidegger, Melanie; Fabisch, Linda; Hatab, Isra; Fickert, Peter; Werring, David; Enzinger, Christian; et al.
Abstract: Background: Non‐alcoholic fatty liver disease and particularly liver fibrosis are related to cardiovascular disease and may indicate an increased risk for atrial fibrillation (AF), but this association has not yet been systematically investigated in a cohort of ischemic stroke patients. Methods: We analyzed data from a prospective single‐center study enrolling all consecutive ischemic stroke patients admitted to our stroke unit over a 1‐year period. All patients received a thorough etiological workup. For evaluation of liver fibrosis, we determined the Fibrosis‐4 (FIB‐4) index, a well‐established noninvasive liver fibrosis test. Laboratory results were analyzed from a uniform blood sample taken at stroke unit admission. Results: Of 414 included patients (mean age 70.2 years, 57.7% male), FIB‐4 indicated advanced liver fibrosis in 92 (22.2%). AF as the underlying stroke mechanism was present in 28.0% (large vessel disease: 25.6%, small vessel disease: 11.4%, cryptogenic: 29.2%). Patients with FIB‐4 ≥ 2.67 had higher rates of AF (53.3% vs. 20.8%, p < 0.001), and this association remained significant after correction for established AF risk factors (odds ratio 2.53, 95% confidence interval 1.44–4.46, p = 0.001). FIB‐4 was further associated with worse functional outcome 3 months ( p < 0.001) and higher mortality 4 years post‐stroke ( p < 0.02), but these relationships were no longer present after correction for age and initial stroke severity. Moreover, FIB‐4 was not associated with long‐term recurrent vascular events. Conclusions: Liver fibrosis assessed by the FIB‐4 index is independently associated with AF in acute ischemic stroke patients. Further studies should evaluate whether adding the FIB‐4 index to AF risk scores increases their precision. Abstract : In this cohort study of 414 consecutive ischemic stroke patients, we found that liver fibrosis as determined by the Fibrosis‐4 (FIB‐4) index was strongly associated with atrial fibrillation as underlying stroke mechanism in multivariable analysis. Therefore, the FIB‐4 index might be used in risk scores for detection of atrial fibrillation in ischemic stroke patients.